Bifunctional Interfacial Regulation with 4‐(Trifluoromethyl) Benzoic Acid to Reduce the Photovoltage Deficit of MAPbI3‐Based Perovskite Solar Cells. Issue 3 (19th January 2022) - Dong, Hongye; Shen, Guibin; Lin, Zhichao; Cai, Qingbin; Li, Yiyi; Xu, Xiangning; Zhang, Wenqi; Mu, Cheng
Abstract: Perovskite solar cells (PSCs), which have recently achieved more than 25% efficiency, are highly promising candidates for renewable energy generation. However, the interface of these solar cells is not yet fully understood. Herein, we used self‐assembled monolayers (SAMs) to regulate the interface of a SnO2 electron transport layer (ETL) and a common MAPbI3 perovskite absorber. Three different monolayers indicate that the contiguous terminal groups and charge distribution of their molecules influence interfacial properties and photovoltaic performance. Aligned energy levels, lower surface tension, and higher quality perovskite crystallization were obtained after SAM regulation. Consequently, applying a 4‐(trifluoromethyl) benzoic acid (BA‐CF3 ) SAM improved the power conversion efficiency (PCE) of the resulting PSC from 16.84% to 18.67%. Moreover, a high open‐circuit voltage ( V OC ) of 1.160 V was achieved with significantly reduced defects and non‐radiative recombination. This work highlights the regulation of these interfaces by a molecule for achieving high‐performance PSCs. Abstract : SnO2 /MAPbI3 interface is regulated with bifunctional 4‐(trifluoromethyl) benzoic acid by self‐assembly, leading to lower surface stress, higher quality perovskite crystallization, and reduced non‐radiative recombination, which reduce the photovoltage deficit of SnO2 /MAPbI3 ‐based perovskite solar cells.